Construction of a high-resolution 2.5-Mb transcript map of the human 6p21.2-6p21.3 region immediately centromeric of the major histocompatibility complex. - Tripodis, N; Palmer, S; Phillips, S; Milne, S; Beck, S; Ragoussis, J (2000)
We have constructed a 2.5-Mb physical and transcription map that spans the human 6p21.2-6p21.3 region and includes the centromeric end of the MHC, using a combination of techniques. In total 88 transcription units including exons, cDNAs, and cDNA contigs were characterized and 60 were confidently positioned on the physical map. These include a number of genes encoding nuclear and splicing factors (Ndr kinase, HSU09564, HSRP20); cell cycle, DNA packaging, and apoptosis related [p21, HMGI(Y), BAK]; immune response (CSBP, SAPK4); transcription activators and zinc finger-containing genes (TEF-5, ZNF76); embryogenesis related (Csa-19); cell signaling (DIPP); structural (HSET), and other genes (TULP1, HSPRARD, DEF-6, EO6811, cyclophilin), as well as a number of RP genes and pseudogenes (RPS10, RPS12-like, RPL12-like, RPL35-like). Furthermore, several novel genes (a Br140-like, a G2S-like, a FBN2-like, a ZNF-like, and B1/KIAA0229) have been identified, as well as cDNAs and cDNA contigs. The detailed map of the gene content of this chromosomal segment provides a number of candidate genes, which may be involved in several biological processes that have been associated with this region, such as spermatogenesis, development, embryogenesis, and neoplasia. The data provide useful tools for synteny studies between mice and humans, for genome structure analysis, gene density comparisons, and studies of nucleotide composition, of different isochores and Giemsa light and Giemsa dark bands.